Gender Dimensions of the COVID-19 Pandemic - de Paz, Carmen; Muller, Miriam; Munoz Boudet, Ana Maria; Gaddis, Isis (World Bank, Washington, DC, 2020)
Experiences from previous pandemics and large-scale shocks show that these crises often affect men and women differently. Specifically, the effectiveness of policy actions and the prevention of costly reversals in the progress achieved towards greater gender equality will crucially depend on how gender considerations are reflected in the examination of potential impacts of and responses to COVID-19. Not only women and girls can be expected to be impacted differently, but they can also play different roles in the response vis-à-vis men and boys that could enhance the likelihood of success.